Severe Flexor Digitorum Profundus Muscular Adhesion by Pseudo-Volkmann's Contracture without Fracture: A Case Report and Literature Review - Jae Woo Kim; Jong Chan Kim; Sung Hoon Koh; Jin Soo Kim; Si Young Roh; Kyung Jin Lee; Dong Chul Lee (Archives of Plastic Surgery)
Volkmann's ischemic contracture is a condition characterized by permanent ischemic damage to muscles and nerves due to vascular insufficiency, resulting in flexion contractures of the affected limb. In contrast, pseudo-Volkmann's contracture presents with similar clinical features but lacks ischemic damage and has the potential for complete recovery. We report a case of a 39-year-old man who developed failure of extension in the middle and ring fingers of the left hand following blunt forearm trauma from a rolling machine. Despite no skin breakage or fracture, his symptoms progressively worsened over 2 months without treatment. Surgical exploration 2 years later revealed severe adhesions of the flexor digitorum profundus muscle at the myotendinous junction to the ulnar periosteum, with immediate recovery after release. This case highlights pseudo-Volkmann's contracture in an adult without fracture, likely due to blunt trauma causing delayed adhesion formation.